2021
DOI: 10.3390/microorganisms9112207
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Proteo-Transcriptomic Changes in the Immediate Early-Phase of Lentiviral Transduction

Abstract: Lentivirus-based vectors derived from human immunodeficiency viruses type 1 and 2 (HIV-1 and 2) are widely used tools in research and may also be utilized in clinical settings. Like their parental virions, they are known to depend on the cellular machinery for successful gene delivery and integration. While most of the studies on cellular proteomic and transcriptomic changes have focused on the late phase of the transduction, studies of those changes in early time-points, especially in the case of HIV-2 based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…Chen et al 39 found that silencing EIF3CL downregulated phosphorylation of adenosine 5′‐monophosphate‐activated protein kinase α and nuclear factor kappa‐B p65, inhibited diffuse intrinsic pontine glioma cell proliferation and anchorage‐independent growth, and induced tumor cell apoptosis. Transcriptome analysis of human embryonic kidney cells transduced with human immunodeficiency viruses type 1 (HIV‐1) and 2 vesicular stomatitis virus G protein pseudotyped lentiviral vectors for 2 h found that EIF3CL was significantly upregulated after HIV‐2 transduction compared with HIV‐1 40 . At present, the research on EIF3CL and 1,25(OH) 2 D 3 needs to be further developed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chen et al 39 found that silencing EIF3CL downregulated phosphorylation of adenosine 5′‐monophosphate‐activated protein kinase α and nuclear factor kappa‐B p65, inhibited diffuse intrinsic pontine glioma cell proliferation and anchorage‐independent growth, and induced tumor cell apoptosis. Transcriptome analysis of human embryonic kidney cells transduced with human immunodeficiency viruses type 1 (HIV‐1) and 2 vesicular stomatitis virus G protein pseudotyped lentiviral vectors for 2 h found that EIF3CL was significantly upregulated after HIV‐2 transduction compared with HIV‐1 40 . At present, the research on EIF3CL and 1,25(OH) 2 D 3 needs to be further developed.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome analysis of human embryonic kidney cells transduced with human immunodeficiency viruses type 1 (HIV-1) and 2 vesicular stomatitis virus G protein pseudotyped lentiviral vectors for 2 h found that EIF3CL was significantly upregulated after HIV-2 transduction compared with HIV-1. 40 At present, the research on EIF3CL and 1,25(OH) 2 D 3 needs to be further developed. ABCD2 is involved in the transport of long-chain and very longchain fatty acids (VLCFA) or their coenzyme A derivatives into peroxisomes with different substrate specificity.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous publication, we described that changes generated by transduction with HIV-2 pseudovirions were significantly different from those generated by HIV-1 [ 43 ]. Indeed, this pattern was also noticed in later time-points as well.…”
Section: Discussionmentioning
confidence: 99%
“…We expected the mutant gene to be transcribed into truncated transcripts that would not be translated, resulting in a functional knockout of ASCL1. To account for possible changes in the cell transcriptome caused by the transduction of lentiviral vectors [21], we also obtained a control cell line stably expressing sgRNA not directed against any of the targets in the human genome (non-target control, NTC). Given the role of ASCL1 in early neurodevelopment, these data suggest that ASCL1 is a promising candidate gene whose dysfunction leads to early events predisposing to SZ or other neuropsychiatric disorders.…”
Section: Generation Of the Mutant Sh-sy5y Line With Ascl1 Partial Del...mentioning
confidence: 99%
“…We expected the mutant gene to be transcribed into truncated transcripts that would not be translated, resulting in a functional knockout of ASCL1. To account for possible changes in the cell transcriptome caused by the transduction of lentiviral vectors [21], we also obtained a control cell line stably expressing sgRNA not directed against any of the targets in the human genome (non-target control, NTC).…”
Section: Generation Of the Mutant Sh-sy5y Line With Ascl1 Partial Del...mentioning
confidence: 99%